Effectiveness of strategies to encourage general practitioners to accept an offer of free access to online evidence-based information: a randomised controlled trial - Buchan, Heather (BioMed Central, 2009)
BACKGROUND: This study examined the effectiveness of seven different interventions designed to increase the proportion of general practitioners (GPs) accepting an offer of free access to an online evidence-based resource. METHODS: Australian GPs (n = 14,000) were randomly selected and assigned to seven intervention groups, with each receiving a different letter. Seven different strategies were used to encourage GPs to accept an offer of two years free access to an online evidence-based resource (BMJ Clinical Evidence). The first group received a standard letter of offer with no experimental demands. Groups two to seven received a standard letter of offer outlining the requirements of the study. They were asked to complete an initial online questionnaire, agree to complete a 12-month follow-up questionnaire, and agree to having data about their usage of the online evidence-based resource provided to researchers. Groups three to seven also had additional interventions included in the letter of offer: access to an online tutorial in use of the resource (group three); provision of a pamphlet with statements from influential opinion leaders endorsing the resource (group four); offer of eligibility to receive professional development points (group five); offer of eligibility for a prize of $500 for registration at a medical conference of their choice (group six); and a combination of some of the above interventions (group seven). RESULTS: In the group with no research demands, 27% accepted the offer. Average acceptance across all other groups was 10%. There was no advantage in using additional strategies such as financial incentives, opinion leader support, offer of professional development points, or an educational aid over a standard letter of offer to increase acceptance rates. CONCLUSION: This study showed low acceptance rates of the offer of access to the online resource when there was an associated requirement of response to a short online questionnaire and non-obtrusive monitoring of GP behaviour in terms of accessing the resource. If we are to improve care and encourage evidence-based practice, we need to find effective ways of motivating doctors and other health professionals to take part in research that can inform our implementation efforts.